AFRICAN MUSIC: A PAN-AFRICAN ANNOTATED BIBLIOGRAPHY, by Carol Lems-Dworkin, Hans Zell Publishers, London, 1991, xvii + 382pp, 2 indexes. - Tracey, Andrew (International Library of African Music, 1996)
pages: 117
Keywords: African Music